Epidemiological characterization of whooping cough in the province of Huancavelica, period 2017 – 2018 - Reginaldo-Huamaní, Rafael (2020)
Objective: to determine the epidemiological characteristics of the whooping cough in the Province of Huancavelica, period 2017-2018. Methodology: a non-experimental cross-descriptive study was carried out; Sample: The data were collected from the total of epidemiological investigation files of probable cases of whooping cough in children less than 5 years of age from the Huancavelica Regional Health Directorate presented from January 2017 to December 2018. Results: the 87.5% of cases occurred in children under 01 years, the ratio of men and women was 5/4, the 55% were from the rural area; the 51% of children had full vaccination for their age, paroxysmal cough was the most frequent sign, although there were also noisy inspiration and vomiting after cough, the 89.8% of cases were treated in hospitalization and in the months of May and June the increase in cases was evident. Conclusion: the whooping cough continues to be a cause of childhood morbidity, being the most vulnerable children under 01 years old, coming from the rural area, without vaccination status or with partial immunization, paroxysmal cough was the characteristic sign and with the highest occurrence in frost period.